Reductions in midlatitude upwelling‐favorable winds implied by weaker large‐scale Pliocene SST gradients. (9th January 2016) - Arnold, Nathan P.; Tziperman, Eli
Abstract: The early‐to‐mid Pliocene (3–5.3 Ma) is the most recent geologic period of significant global warmth. Proxy records of Pliocene sea surface temperature (SST) indicate significant and still unexplained warm anomalies of 3°C–9°C in midlatitude eastern boundary currents, where present‐day cool temperatures are maintained by wind‐driven upwelling. Here we quantify the effect of large‐scale Pliocene‐like SST patterns on the surface wind stress around the California, Humboldt, Canary, and Benguela midlatitude coastal upwelling sites. A high‐resolution atmosphere model forced with Pliocene SST simulates changes in surface winds that imply reductions of 10% to 50% in both coastal upwelling, driven by alongshore wind stress, and offshore upwelling driven by wind stress curl. These changes result primarily from a reduced meridional temperature gradient which weakens the subtropical highs, and a reduction in zonal land‐sea temperature contrast which weakens geostrophic alongshore winds. These results suggest that Pliocene coastal warm anomalies may result in part from atmospheric circulation changes which reduce upwelling intensity. The coastal wind stress and offshore wind stress curl are shown to respond differently to incremental changes in SST, topography, and land surface anomalies. Significant decreases in simulated cloud fraction within the subtropical highs suggest that a weaker land‐sea temperature contrast could be maintained by cloud radiative feedbacks. Key Points: SST‐driven atmosphere circulation change contributes to Pliocene coastal warmth Weak SST gradients reduce upwelling‐favorable wind at midlatitude sites in GCM Decoupling of SST and productivity does not rule out a wind change mechanism